(untitled) (Research, Society and Development, 2022)
Objective: The present study aims to analyze the profile of Research Groups on Nursing Management in Brazil registered in the Directory of the National Council for Scientific and Technological Development (CNPq). That said, we seek to provide concrete data on the distribution, year of creation and the institutions to which they are linked. Methodology: This is a descriptive-analytical study, with a quantitative approach using scientometrics. The research was carried out in three stages. The first step consisted of the parameterized search, in the current database, with the search term “Nursing Management”, the second step related to the selection of each group within the management line with certified status and the third step the grouping of the data collected into an excel spreadsheet to enable the mapping. Results and Discussion: We found 71 Research Groups registered in the CNPq Directory, from the last census of the groups. Subsequently, the mining process was carried out, and after excluding the groups in a situation of filling (4 groups), excluded (11 groups), not updated (13 groups) and those not included in the current theme (5 groups), 38 remained. research groups in the area of nursing management. One impediment faced during data collection was the instability of the platform. Conclusion: The quantitative survey totaled 38 research groups in the management line, these, arranged in public higher education institutions. It pointed to a concentration of 42.11% in the state of SP, with USP holding 23.68%. Additionally, it identified the creation of five new groups during the pandemic context and revealed the need to encourage the implementation of these spaces within private universities, isolated colleges, technological education centers and federal technological education centers. It is considered essential to fight for these places of academic insertion, for expansion, preservation and valorization for a more critical and engaged education with the present.